The Research of the Establishing a Design Process Framework for Museum Exhibition Design - Lin, Chung-Hung (IJRDO-Journal of Applied Science, 2015)
Museum exhibition styles have changed remarkably over the past few decadesbecause they have generally followed the evolution of social and cultural circumstancesand the adoption of new technology. Today, exhibition design is important element forestablishing a more professional status for museums and other institutions (Velarde, 1990).The study provides theoretical application by proposing a particular form ofinter-disciplinary museum exhibition design framework. The outcome of this study,therefore, is to create a conceptual design concerning the following approaches will be:(1) A conceptual framework for the design planning that allows designers to cope with thecomplexity of co-ordination between all participants involved museum exhibitiondesign.(2) A multi-disciplinary systematic framework which can be described as a plan of designactivity, particularly for museum exhibition design to achieve design aim.Keywords: museum exhibition, design process framework, inter-disciplinary, curator,multi-disciplinary